Implementasi Mengamankan Pesan Teks Menggunakan Metode GOST (Gosundarstevenny Standard) - Ritonga, Mario Franko Ezra Hasiholan; Kurniawan, Muchamad; Agustini, Siti (Institut Teknologi Adhi Tama Surabaya, 2024)
The increasing development of technology has made it easier for people to communicate with each other. Sometimes, some of the information sent must be kept confidential so that it is not misused by irresponsible people. This research deals with securing messages using the GOST method during information exchange. The output messages of chats converted into ciphertext served as the research materials. The research results indicated that the application to secure text messages successfully implemented encryption and decryption techniques through the GOST method. The more bit changes occurred, the more difficult the cryptographic algorithm was to solve.